2015
DOI: 10.1007/s10995-015-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Planned and Reported Home Infant Sleep Locations Among Mothers of Late Preterm and Term Infants

Abstract: Objective To compare maternal report of planned and practiced home sleep locations of infants born late preterm (34 0/7 to 36 6/7 gestational weeks) with those infants born term (≥ 37 0/7 gestational weeks) over the first postpartum month. Methods Open-ended semi-structured maternal interviews were conducted in a U.S. hospital following birth and by phone at one month postpartum during 2010–2012. Participants were 56 mother-infant dyads: 26 late preterm and 30 term. Results Most women planned to room share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…who had just joined the team to provide data for this exploratory study on the relationship of infant feeding outcomes and maternal emotional well-being and to asses maternal plans and practices for infant sleep locations. 20 Therefore, these measures were administered to about half of the participants (N=53, 26 late preterm and 27 term).…”
Section: Methodsmentioning
confidence: 99%
“…who had just joined the team to provide data for this exploratory study on the relationship of infant feeding outcomes and maternal emotional well-being and to asses maternal plans and practices for infant sleep locations. 20 Therefore, these measures were administered to about half of the participants (N=53, 26 late preterm and 27 term).…”
Section: Methodsmentioning
confidence: 99%
“…Reasons for parents not following safe sleep recommendations were similar to those for neonatal nurses. In two studies, researchers cited parental preference and infant comfort as reasons that parents stray from safe sleep practices (Fowler et al, 2013;Tully, Holditch-Davis, & Brandon, 2015). Other reasons included fear of infant choking (Fowler et al, 2013) and convenience with nighttime feedings (Tully et al, 2015).…”
Section: Barriers To Compliancementioning
confidence: 99%
“…In two studies, researchers cited parental preference and infant comfort as reasons that parents stray from safe sleep practices (Fowler et al, 2013;Tully, Holditch-Davis, & Brandon, 2015). Other reasons included fear of infant choking (Fowler et al, 2013) and convenience with nighttime feedings (Tully et al, 2015). Tully et al (2015) found a discrepancy between bed-sharing plans and practice, suggesting that maternal expectations for nighttime parenting and infant sleep did not match their actual experiences.…”
Section: Barriers To Compliancementioning
confidence: 99%
“…Women may be aware of recommendations, such as solitary infant sleep, but adopt different practices for a variety of reasons. Prospective studies have documented that parent-infant bed sharing is more common than anticipated (Tully, Holditch-Davis, & Brandon, 2015;Ball et al, 1999). However, maternal and child health behaviors are often emotionally charged.…”
Section: Innovations In Patient-centered Carementioning
confidence: 99%